2020
DOI: 10.1021/acsestwater.0c00130
|View full text |Cite
|
Sign up to set email alerts
|

The Mobility of Plastic Nanoparticles in Aqueous and Soil Environments: A Critical Review

Abstract: Plastic nanoparticles (PNPs) are now widely recognized as a significant, and ever increasing, hazard in aquatic and soil environments. These particles, defined here as plastics <1000 nm across their largest dimension, are released into the environment both as primary products and through the degradation of larger plastic waste. They have the potential to be highly mobile, given their small size, which raises concerns about their global spread. Furthermore, PNPs are capable of adsorbing a variety of other pollu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 75 publications
1
38
0
1
Order By: Relevance
“…As sediment is the main sink for most types of microplastics (Scherer et al 2020), including tire rubber (Marwood et al 2011), studies that explore their behaviour and toxicity in this environmental matrix are a priority. Similar to what has been observed with other microplastic particles, it is likely that the microrubber particles form homo-and heteroaggregates with other biogenic and inorganic particles and, depending on the density of the particles and of the final aggregate, increase their sinking rates (Brewer et al 2021;Michels et al 2018). These processes are enhanced if the microplastics have been previously covered by biofilm.…”
Section: Toxicity Of Tire Rubber To Lumbriculus Variegatus and Chironomus Ripariussupporting
confidence: 66%
“…As sediment is the main sink for most types of microplastics (Scherer et al 2020), including tire rubber (Marwood et al 2011), studies that explore their behaviour and toxicity in this environmental matrix are a priority. Similar to what has been observed with other microplastic particles, it is likely that the microrubber particles form homo-and heteroaggregates with other biogenic and inorganic particles and, depending on the density of the particles and of the final aggregate, increase their sinking rates (Brewer et al 2021;Michels et al 2018). These processes are enhanced if the microplastics have been previously covered by biofilm.…”
Section: Toxicity Of Tire Rubber To Lumbriculus Variegatus and Chironomus Ripariussupporting
confidence: 66%
“…This discrepancy could be explained by the different strains of M. aeruginosa and/or the different sizes of PS-NH 2 beads used, which may change its toxicity, uptake threshold, and retention time. ,− Indeed, other properties that vary across nanoplastics, including shape, parent material, or surface charge, could alter biological effects, and we recommend these sources of variation be given greater consideration in future research. For example, our particles are likely to have been positively charged, ,, but particles vary in charge in the environment, − with negatively charged particles often having weakened biological effects. ,, Therefore, our results may represent stronger than average effects of nanoplastics on cyanoHAB control.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have already reported a relationship between size and recovery rate highlighting that separation of particles with diameters lower than one mm is more difficult than large MPs [ 27 , 46 , 47 ]. Electrostatic interactions between MPs and other particles depend on the morphology, composition, size, and surface charge of MPs [ 48 ]. Therefore, the presence of the matrix can interfere with the MPs extraction phase from the soil and our study suggests this with the recovery of 100% of PET, in the absence of soil.…”
Section: Discussionmentioning
confidence: 99%